PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION ) TERHADAP HASIL BELAJAR CHEST PASS BOLABASKET. (STUDI PADA SISWA KELAS X SMA NEGERI 1 KOTA PROBOLINGGO) - HAMDANI AKBAR, RIZAL (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The cooperative learning model in TGT type is one of learning models which is putting the student in a small groups that consist 5 - 7 students and involving some students as the tutor. Where as, direct instruction (DI) is a learning model which is centered on the teacher. The material is gradually delivered to the srudent and then the teacher leads them in training. That learning result of chest pass is being defined as students behavior changing based on the experiment after receiving that learning and viewing on the result of the test. After passing those two learning models, there is hope that it will help students in developing and upgrading students ability in chest pass. Purpose of this research is to know is there any effect and how big the influence of those two models in chest pass learning result. This is an experimental research with randomized control pre test and post test as the design. Population of this research is 192 students from X class SMAN 1 Probolinggo. Technique that use for sampling is cluster random sampling with 55 sample test. 30 second wall pass test become the instrument. In analyze the data, researcher uses t-test. Based on analysis result, it is knowing that average result for pre test on TGT group is 9,86 with deviation standard 4,92. Then , 12,89 for post test on TGT with deviation standard 6,585. For pre test on DI the average is 10,04 with deviation stansart 11,89. Then, 11,89 for post test with deviation standard 6,612. Next the result of paired t test on TGT group is tcount is more than ttable (tcount 6,993 > ttable 2,010), so it can be concluded that there is an effect of TGT type on chest pass learning result. Then, after another paired t test on DI group, it is revealed that tcount 3,359 with significance 0,002. So it is appeared to the surface that tcount is bigger than  ttable  (tcount 3,359 > ttable 2,010), so it can be concluded that direct instruction has an impact on the result chest pass learning result. Thus, based on those test and result, it can be concluded that TGT and DI learning models influence the students learning result of chest pass in X class SMAN 1 Probolinggo. Keywords: Cooperative learning Teams Games Tournament (TGT), Direct Instruction (DI), chest pass learning result.